On Fault-Tolerant Data Placement in Storage Networks - Mense, Mario

Kostenoptimale Kapazitätsabstimmung in einer getakteten Variantenfließlinie unter expliziter Berücksichtigung des Unterstützereinsatzes und unterschiedlicher Planungszeiträume - Altemeier, Simon

A combined simulation and optimization based method for predictive-reactive scheduling of flexible production systems subject to execution exceptions - Mahajan, Kiran

Methode zur Klassifikation und Entwicklung reifegradbasierter leistungsbewertungs- und Leistungssteigerungsmodelle - Christiansen, Sven-Kelana

5. Symposium für Vorausschau und Technologieplanung - Gausemeier, Jürgen

Ressourceneffiziente Realisierung Pulscodierter Neuronaler Netze - Kaulmann, Tim

An Aspect-Oriented Model-Driven Engineering Approach for Distributes Embedded Real-Time Systems - Wehrmeister, Marco A.

Assessing the Cost of Assortment Complexity in Consumer Goods Supply Chains by Reconfiguration of Inventory and Production Planning Parameters in Response to Assortment Changes - Danne, Christoph

Planung und Konzipierung von Marktleistungen - Stoll, Karsten

Standortwahl als Entscheidungsproblem des Logistikcontrollings - Betz, Stefan (Der Betriebswirt)

Interfacial energy estimation in a precipitation reaction using the flatness based control of the moment trajectories - Vassilev, Vassil; Gröschel, Michael; Schmid, Hans-Joachim; Peukert, Wolfgang; Leugering, Günter (Chemical Engineering Science)
In this paper, we consider a model for precipitation experiments based on the population balance equation. The study revealed a high sensitivity of the system with respect to the modeling of intrinsic parameters, motivating a comprehensive validation of the estimates. In the forward simulation the impact of the influencing parameters including surface energy, nucleus size and distribution is investigated. Subsequently we construct a simplified model of the precipitation process in such a way that it is orbitally flat in terms of control theory, which enables the inverse calculation of the parameters. The numerical results of the inverse simulation for the interfacial energy have been compared to a physical model. The possibility of solving the inverse problem provides a promising way of estimating hardly measurable quantities for more complex molecules.

Simulation of structure and mobility of aggregates formed by simultaneous coagulation, sintering and surface growth - Al Zaitone, Belal; Schmid, Hans-Joachim; Peukert, Wolfgang (Journal of Aerosol Science)
In this work, a new model for the simulation of nanostructured aggregates by simultaneous coagulation, sintering and surface growth is presented. Coagulation is treated as cluster–cluster agglomeration along the line connecting the center of mass of both agglomerates and is implemented using a Monte Carlo algorithm. Sintering is modeled as successive overlapping of spheres which cause reduction in the surface area based on a rate law for surface reduction. Surface growth is modeled as an increase in primary particle diameter, e.g. as a result of surface reactions. The evolved aggregates are analyzed by calculating their fractal dimension, radius of gyration, mobility diameter and mobility shape factor. It is found that the aggregates structure tends to be more compact when introducing the surface growth in shorter time comparing to the coagulation-sintering step only. Fractal dimension and the mobility shape factor of the resulting aggregates are correlated to an effective dimensionless time that combines the characteristic times of these three fundamental mechanisms. It is shown that the mobility diameter in the free molecular regime is not proportional to the radius of gyration. A power law relation that correlates the aggregates projected area and the equivalent number of primary particles is found to be in a very good agreement with estimates published in literature.

Liquid–liquid phase transfer of magnetite nanoparticles - Machunsky, Stefanie; Grimm, Philipp; Schmid, Hans-Joachim; Peuker, Urs A. (Colloids and Surfaces A: Physicochemical and Engineering Aspects)
The study presents first experimental results of the transfer of magnetite nanoparticles from an aqueous to a second non-miscible non-aqueous liquid phase. The transfer is based on the adsorption of macromolecular surfactants onto the particle surface at the liquid–liquid interface. For a successful direct phase transfer, it is essential to have cations, like ammonium ions, present in the aqueous phase as well as a threshold concentration of surfactant in the organic liquid phase. While penetrating the liquid–liquid interface, the particles are covered with the surfactant and therefore a partial de-agglomeration is initiated. Based on literature and experimental data a mechanism of surfactant adsorption is proposed. The competing adsorption of the surfactant molecules at the liquid–liquid interface leads to the formation of emulsions and therefore to a hindrance for particles passing the interface. Nevertheless a high efficiency of 100% yield can be reached using optimized process parameters for the phase transfer process.

Three-dimensional simulation of viscous-flow agglomerate sintering - Kirchhof, M. J.; Schmid, Hans-Joachim; Peukert, W. (Physical Review E)
The viscous-flow sintering of different agglomerate particle morphologies is studied by three-dimensional computer simulations based on the concept of fractional volume of fluid. For a fundamental understanding of particle sintering characteristics, the neck growth kinetics in agglomerate chains and in doublets consisting of differently sized primary particles is investigated. Results show that different sintering contacts in agglomerates even during the first stages are not completely independent from each other, even though differences are small. The neck growth kinetics of differently sized primary particles is determined by the smaller one up to a size difference by a factor of approximately 2, whereas for larger size differences, the kinetics becomes faster. In particular, the agglomerate sintering kinetics is investigated for particle chains of different lengths and for different particle morphologies each having ten primary particles and nine initial sintering contacts. For agglomerate chains, the kinetics approximately can be normalized by using the radius of the fully coalesced sphere. In general, different agglomerate morphologies show equal kinetics during the first sintering stages, whereas during advanced stages, compact morphologies show significantly faster sintering progress than more open morphologies. Hence, the overall kinetics cannot be described by simply using constant morphology correction factors such as fractal dimension or mean coordination number which are used in common sintering models. However, for the first stages of viscous-flow agglomerate sintering, which are the most important for many particle processes, a sintering equation is presented. Although we use agglomerates consisting of spherical primary particles, our methodology can be applied to other aggregate geometries as well.

Geregelte Vereinfachung hierarchischer Partitionen von Modellen in der Materialflusssimulation - Huber, Daniel

Verifying continuous-variable entanglement in finite spaces - Sperling, Jan; Vogel, W. (Physical Review A)

Representation of entanglement by negative quasiprobabilities - Sperling, Jan; Vogel, W. (Physical Review A)

Necessary and sufficient conditions for bipartite entanglement - Sperling, Jan; Vogel, W. (Physical Review A)

Optimale Darlehensbündel in der privaten Immobilienfinanzierung - Dzienziol, J.; Kundisch, Dennis (Kredit und Kapital)

Zur Preissetzung verschiedener Emittenten bei Indexzertifikaten auf den DAX - Kundisch, Dennis; Klein, C. (Zeitschrift für Bankrecht und Bankwirtschaft)

Der Tracking Error von indexnachbildenden Instrumenten auf den DAX - eine empirische Analyse des ETFs DAX EX sowie zehn Indexzertifikaten - Kundisch, Dennis; Klein, C. (Der Betrieb)

Lernstrategien im Grundschulalter. Konzepte, Befunde und praktische Implikationen

Diagnose mathematischer Basiskompetenzen im Kindergarten - Höntges, Jens; Günther, Frederike; Hellmich, Frank (Beiträge zum Mathematikunterricht 2009)

Lesestrategien und Lesekompetenzen bei Kindern am Ende der Grundschulzeit - Hellmich, Frank; Läsche, Johannes (Europäisierung der Bildung. Konsequenzen und Herausforderungen für die Grundschulpädagogik)

Mathematische Basiskompetenzen im Vorschulalter erkennen und deuten - Hellmich, Frank (MNU-PRIMAr)

Was sind Lernstrategien ... und warum sind sie wichtig? - Wernke, Stephan; Hellmich, Frank (Lernstrategien im Grundschulalter. Konzepte, Befunde und praktische Implikationen)

Möglichkeiten der Erfassung von Lesestrategien im Leseunterricht der Grundschule - Hellmich, Frank; Höntges, Jens (Lernstrategien im Grundschulalter. Konzepte, Befunde und praktische Implikationen)

Body fat and animal protein intakes are associated with adrenal androgen secretion in children - Shi, Lijie; Wudy, Stefan A; Buyken, Anette; Hartmann, Michaela F; Remer, Thomas (The American Journal of Clinical Nutrition)

Birth and early life influences on the timing of puberty onset: results from the DONALD (DOrtmund Nutritional and Anthropometric Longitudinally Designed) Study - Karaolis-Danckert, Nadina; Buyken, Anette; Sonntag, Antje; Kroke, Anja (The American Journal of Clinical Nutrition)

Diet Quality in Childhood Is Prospectively Associated with the Timing of Puberty but Not with Body Composition at Puberty Onset - Cheng, Guo; Gerlach, Steffi; Libuda, Lars; Kranz, Sibylle; Günther, Anke L. B.; Karaolis-Danckert, Nadina; Kroke, Anja; Buyken, Anette (The Journal of Nutrition)

Dietary Protein Intake throughout Childhood Is Associated with the Timing of Puberty - Günther, Anke L. B.; Karaolis-Danckert, Nadina; Kroke, Anja; Remer, Thomas; Buyken, Anette (The Journal of Nutrition)

Compositional CSP Traces Refinement Checking - Wehrheim, Heike; Wonisch, Daniel (Electr. Notes Theor. Comput. Sci.)

Static Class Elements for Object-Z - Ruhroth, Thomas; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Measure, Diagnose, Refactor: A Formal Quality Cycle for Software Models - Ruhroth, Thomas; Voigt, Hendrik; Wehrheim, Heike (35th Euromicro Conference on Software Engineering and Advanced Applications, SEAA 2009, Patras, Greece, August 27-29, 2009, Proceedings)

Integrated Formal Methods, 7th International Conference, IFM 2009, Düsseldorf, Germany, February 16-19, 2009. Proceedings

Productivity management for customer solutions --- Towards a performance management system for efficient service value networks - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Knackstedt, Ralf; Nüttgens, Markus; Thomas, Oliver; Fellmann, Michael (29th International RESER Conference)

Configurative Service Engineering --- A Rule-Based Configuration Approach for Versatile Service Processes in Corrective Maintenance - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin (Proceedings of the 42th Hawaii International Conference on System Sciences)

A Framework for Design Research in the Service Science Discipline - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Americas Conference on Information Systems)

Design Requirements to Support Information Flows for Providing Customer Solutions: A Case Study in the Mechanical Engineering Sector - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Proceedings of the First International Symposium on Services Science (ISSS'09))

Model-Based Decision Support for the Customer-Specific Configuration of Value Bundles - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Enterprise Modelling and Information Systems Architectures)

Professional learning and TVET: challenges and perspectives for teachers and instructors - Harteis, Christian (International handbook of education for the changing World of Work)

Lernen von Lehrenden im Arbeitsprozess - Mulder, Regina H; Harteis, Christian; Gruber, Hans (Lehrprofessionalität - Bedingungen, Genese, Wirkungen und Messung)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Wirtschaft und Betrieb - Heid, Helmut; Harteis, Christian (Handbuch Bildungsforschung)

Hierarchisches Clustering mit minimalen Cluster-Durchmessern - Schröer, Carsten

Teacher Collaboration Concerning ICT-Use and its Essential Conditions - Schulz-Zander, Renate; Eickelmann, Birgit (Proceedings – 9th WCCE. IFIP World Conference on Computers in Education)

E-teaching plus. Die webbasierte Lernumgebung für situiertes Lernen mit Unterrichtsvideos - Schulz-Zander, Renate; Eickelmann, Birgit

National Policies and Practices on ICT in Education: Germany - Schulz-Zander, Renate; Eickelmann, Birgit (Cross-national Information and Communication Technology. Policies and Practices in Education)

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij

Die Schwierigkeit des k-Median Clusterings für Bregman-Divergenzen - Scholz, Christoph

Algorithms for the Bregman k-Median Problem - Ackermann, Marcel Rudolf

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Coresets and Approximate Clustering for Bregman Divergences - Ackermann, Marcel R.; Blömer, Johannes (Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms)

Sampling methods for shortest vectors, closest vectors and successive minima - Blömer, Johannes; Naewe, Stefanie (Theoretical Computer Science)
Keywords: Geometry of numbers; Lattices; Shortest vectors

Three-Valued Spotlight Abstractions - Schrieb, Jonas; Wehrheim, Heike; Wonisch, Daniel (FM 2009: Formal Methods)

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (Advances in Cryptology - ASIACRYPT 2009, 15th International Conference on the Theory and Application of Cryptology and Information Security, Tokyo, Japan, December 6-10, 2009. Proceedings)

Modifications in Dietary Fat Quality Are Associated with Changes in Serum Lipids of Older Adults Independently of Lipid Medication - Buyken, Anette; Flood, Victoria; Rochtchina, Elena; Nestel, Paul; Brand-Miller, Jennie; Mitchell, Paul (The Journal of Nutrition)

Immigrational Background Affects the Effectiveness of a School-based Overweight Prevention Program Promoting Water Consumption - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Toschke, André M.; Reinehr, Thomas; Kersting, Mathilde (Obesity)

Relative validity of a self-completion 24 h recall questionnaire to assess beverage consumption among schoolchildren aged 7 to 9 years - Muckelbauer, Rebecca; Libuda, Lars; Kersting, Mathilde (Public Health Nutrition)
Abstract Objective Drinking habits in children are associated with diet quality, but validated assessment tools for large-scale studies in young children are lacking. Therefore, we validated a self-completion 24 h recall questionnaire (RQ) focusing on beverage consumption with a 24 h weighed record (WR). Design Thirty-five voluntary participants from the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study cohort aged 7–9 years completed the RQ. The illustrated RQ required ticking the number of glasses of seven beverage categories consumed in five time intervals in the previous 24 h. As a reference, parents completed weighed records of their child’s diet. Agreement between the RQ and WR was tested by classification into consumers and non-consumers (kappa coefficients, κ ), by the children’s ability to estimate the exact beverage and total volume consumed (Wilcoxon signed-rank test, Spearman rank correlation), and by ranking children according to reported beverage volumes. Results The RQ and WR showed a good level of agreement for classifying participants into consumers and non-consumers of the single beverage categories ( κ values between 0·78 and 0·94). Correlation coefficients for the volume of the single categories ranged between 0·81 and 0·91. The total beverage volume was overestimated in the RQ, on average, by 114 ml ( P = 0·015). Agreement in ranking into tertiles by beverage volume was moderate to good for juice/soft drinks ( κ = 0·44), milk ( κ = 0·57) and water ( κ = 0·70), but fair for the total beverage volume ( κ = 0·23). Conclusions Our self-completion 24 h RQ could estimate the consumption of several beverage categories among young children at the group level, but quantification of total beverage volume was flawed.

Relation of Dietary Glycemic Index, Glycemic Load, and Fiber and Whole-Grain Intakes During Puberty to the Concurrent Development of Percent Body Fat and Body Mass Index - Cheng, G.; Karaolis-Danckert, N.; Libuda, Lars; Bolzenius, K.; Remer, T.; Buyken, Anette E. (American Journal of Epidemiology)

Long-term process evaluation of a school-based programme for overweight prevention - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Child: Care, Health and Development)

A Simple Dietary Intervention in the School Setting Decreased Incidence of Overweight in Children - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Reinehr, Thomas; Kersting, Mathilde (Obesity Facts)

Promotion and Provision of Drinking Water in Schools for Overweight Prevention: Randomized, Controlled Cluster Trial - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Toschke, A. M.; Reinehr, T.; Kersting, M. (PEDIATRICS)

Erfolgreich Computer und Internet in Grundschulen integrieren – eine empirische Analyse aus Sicht der Schulentwicklungsforschung - Eickelmann, Birgit; Schulz-Zander, Renate; Gerick, Julia (Europäisierung der Bildung - Konsequenzen und Herausforderungen für die Grundschulpädagogik)

The Dagstuhl Core - Dumitrescu, Theodor; Kepper, Johannes; Kornstädt, Andreas; Röwenstrunk, Daniel; Roland, Perry; Sapp, Craig; Selfridge-Field, Eleanor; Wiering, Frans; Wiggins, Geraint A.

Soft drinks and body weight development in childhood: is there a relationship? - Libuda, Lars; Kersting, Mathilde (Current Opinion in Clinical Nutrition and Metabolic Care)

Getränkeverzehr und Übergewicht bei Kindern - Libuda, Lars; Muckelbauer, R.; Kersting, M. (Journal für Ernährungsmedizin)

Einfluss des Konsums von Erfrischungsgetränken auf den Ernährungs- und Gesundheits¬status von Kindern - Libuda, Lars (Ernährungsumschau)

DONALD News: Zusammenhang zwischen dem Verzehr von Erfrischungsgetränken und dem Knochenstatus von Kindern und Jugendlichen. - Libuda, Lars; Remer, Thomas; Kersting, M. (Ernährungsumschau)

Associations of fat and cholesterol intake with serum lipid levels and cardiovascular disease: The EURODIAB IDDM Complications Study* - Toeller, M.; Buyken, Anette; Heitkamp, G.; Scherbaum, W.A.; Krans, H.M.J; Fuller, J.H. (Experimental and Clinical Endocrinology & Diabetes)

A new FFQ designed to measure the intake of fatty acids and antioxidants in children - Stiegler, Petra; Sausenthaler, Stefanie; Buyken, Anette; Rzehak, Peter; Czech, Daniel; Linseisen, Jakob; Kroke, Anja; Gedrich, Kurt; Robertson, Claire; Heinrich, Joachim (Public Health Nutrition)
Abstract Objective The present paper describes the systematic development of an FFQ to assess the intake of fatty acids and antioxidants in school-aged children. In addition, a validation study applying 24 h dietary recalls was performed. Design Using the variance-based Max_r method, a list of eighty-two foods was compiled from data obtained by 3 d weighed dietary records. The foods were used to design an FFQ, the comprehensibility of which was evaluated in a feasibility study. In addition, the FFQ was validated in a subset of 101 children from the German Infant Nutritional Intervention Study (GINI PLUS) against one 24 h dietary recall. Results The feasibility study attested a good acceptance of the FFQ. Mean intake of foods compared well between the FFQ and the 24 h dietary recall, although intake data generated from the FFQ tended to be higher. This difference became less apparent at the nutrient level, although the estimated average consumption of arachidonic acid and EPA using the FFQ still exceeded values recorded with the 24 h recall method by 45 % and 29 %, respectively. Conclusions On the basis of the systematic selection process of the food list, the established practicability of the FFQ and the overall plausibility of the results, the use of this FFQ is justified in future epidemiological studies.

Glucocorticoids and body fat associated with renal uric acid and oxalate, but not calcium excretion, in healthy children - Shi, Lijie; Berkemeyer, Shoma; Buyken, Anette; Maser-Gluth, Christiane; Remer, Thomas (Metabolism)

Glycemic index in overweight development: distinguishing limited evidence from limits in evidence - Buyken, Anette; Günther, Anke LB; Barclay, Alan; Brand-Miller, Jennie; Schulze, Matthias B (The American Journal of Clinical Nutrition)

IT Productivity and Aggregation using Income Accounting - Kundisch, Dennis; Mittal, N.; Nault, B. (10th Workshop on Information Systems and Economics (WISE))

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach considering Social Capital in the private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Proceedings of the 15th Amercas Conference on Information Systems (AMCIS))

An Evaluation Framework for Tracker Certificates during the Financial Crisis and beyond - Kundisch, Dennis; Klein, C. (International Federation of Classification Societies 2009 Conference)

Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Rezension zu L.J. Issing & P. Klimsa (Hrsg.) (2009). Online-Lernen. Handbuch für Wissenschaft und Praxis. München: Oldenbourg Verlag - Eickelmann, Birgit (Journal for Educational Research Online)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Selbstoptimierende Systeme des Maschinenbaus - Definitionen, Anwendungen, Konzepte - Adelt, P.; Donoth, J.; Gausemeier, Jürgen; Henkeler, S.; Kahl, S.; Klöpper, B.; Krupp, A.; Münch, E.; Oberthür, S.; Paiz, C.; Porrmann, M.; Radkowski, R.; et al.

Verlässlichkeit selbstoptimierender Systeme - Potenziale nutzen und Risiken vermeiden - Dell'Aere, A.; Hirsch, M.; Klöpper, B.; Koester, M.; Krüger, M.; Krupp, A.; Müller, T.; Oberthür, S.; Pook, S.; Priesterjahn, C.; Romaus, C.; Schmidt, A.; et al.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Musterbasiertes Re-Engineering von Softwaresystemen - Meyer, Matthias

Dienste-Infrastrukturen für eLearning – Konzeption, Aufbau und Betrieb - Brennecke, Andreas; Finke, Stefan; Oevel, Gudrun; Roth, A. (Hochschulentwicklung innovativ gestalten – Das Projekt Locomotion an der Universität Paderborn)

Ultranarrow coupling-induced transparency bands in hybrid plasmonic systems - Zentgraf, Thomas; Zhang, Shuang; Oulton, Rupert F.; Zhang, Xiang (Physical Review B)

Plasmon lasers at deep subwavelength scale - Oulton, Rupert F.; Sorger, Volker J.; Zentgraf, Thomas; Ma, Ren-Min; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Nature)

An optical cloak made of dielectrics - Valentine, Jason; Li, Jensen; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nature Materials)

Self-Organisation and Self-Optimization - Meyer auf der Heide, Friedhelm; Rammig, Franz-Josef (Public Service Review: Science and Technology)

Language and Logic in German Post-Hegelian Philosophy - Peckhaus, Volker (The Baltic International Yearbook of Cognition, Logic and Communication, Bd. 4: 200 Years of Analytical Philosophy)

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Algorithmische und komplexitätstheoretische Aspekte kombinatorischer Preisoptimierung (Computational Aspects of Combinatorial Pricing Problems) - Briest, Patrick (it - Information Technology)

Die Welterbeliste - zwischen Kanonbildung und Kanonverschiebung - Seng, Eva- Maria
Demnächst in: ZS ejournal Kunstgeschichte, LMU München. Open Peer Reviewed Journal www.kunstgeschichte-ejournal.net